PENGARUH MODAL USAHA TERHADAP SIKAP BERWIRAUSAHA (Studi Empiris Di Kelurahan Tanjung Rejo Kecamatan Medan Sunggal) - Tambunan, Formaida (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2021)
A business will need capital continuously to develop a business that connects the tools, materials and services used in production to obtain sales results so that business capital is one of the aspects that must exist in entrepreneurship. The purpose of this study was to analyze the effect of venture capital on entrepreneurial attitudes (Empirical Study in Tanjung Rejo Village, Medan Sunggal Subdistrict). The study population was all entrepreneurs in the area of Tanjung Rejo Village, Medan Sunggal Subdistrict) and the sample using the Slovin formula obtained 58 respondents with the sampling technique used was simple random sampling. Data analysis using linear regression analysis. The results showed that venture capital had an effect on entrepreneurial attitudes with tcount = 2.246 ttable = 2.003 and p value = 0.029 Î± = 0.05. Suggestions given are for people who want to improve the family economy to make a business that is really well planned which can be started by striving for venture capital so that it can respond to entrepreneurship.